Політичні наслідки феномена інформаційних технологій як передумови розвитку інноваційних якостей особистості - Бубнов, І. В.; Бубнов, И. В.; Bubnov, I.; Халілова-Чуваєва, Ю. О.; Халилова-Чуваева, Ю. О.; Halilova-Chuvaeva, Ju. (My University, 2012)
The article deals with the phenomenological impact of information technology on creation of the conditions, formation of the possibilities and prospects of evelopment of innovative person. The attempt is made to identify speciﬁ c national factors that contribute the improving of innovative person, analyzed some of the political consequences of this phenomenon.
Бубнов І. В., Халілова-Чуваєва Ю. О. Політичні наслідки феномена інформаційних технологій як передумови розвитку інноваційних якостей особистості / І. В Бубнов, Ю. О. Халілова-Чуваєва // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 184-196.
Keywords: інформаційні технології; наслідки феномена; розвиток інноваційних якостей особистості; информационные технологии; последствия феномена; развитие инновационных качеств личности; information Technology; the consequences of the phenomenon; development of innovative qualities of the person